UJI EFEKTIVITAS EKSTRAK KULIT BUAH SALAK (Salacca zalacca (Gaertn.) Voss) TERHADAP PENURUNAN KADAR GULA DARAH TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus L.) YANG DIINDUKSI SUKROSA - Kanon, Muharli Qadri; Fatimawali, Fatimawali; Bodhi, Widdhi (PHARMACON, 2012)
This study aimed at finding out the effectivity of Salacca (Salacca zalacca [Gaertn]Voss) rind extract on blood sugar decrease of white male wistar (Rattus norvegicus L.)induced with sucrose. Completely randomized design method was used in this experiment.The subject of the experiment were 15 white male wistar which were divided into 3 (three)groups namely negative control group, treatment group with the dose of 150 mg extract/kgbody weight, and positive control group using glibenclamide 0.45 mg/kg body weight. Dataobtained from the examination of the fasting blood sugar were 30 minutes after inductionwith sucrose and at minute 15, 30, 60, and 120 after treatment was given. The data isprocessed using ANOVA and LSD test to compare between the negative control group,treatment, and a positive control. The analysis revealed a significant difference betweennegative control and treatment, negative control and positive control, but did not show asignificant difference between treatment groups with the positive control. The conclusion ofthis study is Salacca rind extract has an effect on blood sugar levels decrease of white malewistar induced with sucrose.Keywords: Salacca zalacca (Gaertn.) Voss, Salacca rind extract, blood sugar level, sucrose